Analysis of the frequency of the monthly rainfall in the region Junin, Peru - Palomino Zegarra, Liz M. (2021)
This work aimed to perform the analysis of monthly precipitation frequency for the departments of Huancavelica, Junín and Pasco. The analysis of monthly precipitation frequency was carried out with rainfall information evaluated for the period from January 1965 to December 2001 of 19 stations which are distributed according to the climatic characteristics and the homogeneity of the data in the study area, which includes the departments of Huancavelica, Junín and Pasco. Among the results of the study were identified regions that represent the monthly precipitation which are based on probability distribution laws: Exponential, Generalized Pareto, Weibull, Gumbel, GEV, Normal. Log-Normal, Gamma, Pearson type III, Log Pearson and Poisson exponential. The probability distribution laws that fit the monthly precipitation in zone I are Log-Normal and Gamma and for Zone II Gamma and Log-Normal.